Analysis of Determinants of Palm Commodity Supply in West Sulawesi - Muhlis; Syafiuddin; Sri Mardiyati (International Journal of Economics, Business and Innovation Research, 2026)
This study aims to analyze trends in palm oil production, analyze factors influencing palm oil supply, and determine the elasticity of palm oil supply in West Sulawesi. The research method used is quantitative descriptive. The study was conducted in West Sulawesi. The data used is time series data from 2004 to 2024, spanning 20 years. Data analysis used includes trend analysis, multiple linear regression analysis, and the supply elasticity formula.The results show an increasing trend in palm oil production from 2004 to 2024, although annual data shows a fluctuation pattern of 0.4198, or 41.98 percent per year, equivalent to 0.028 units of production per year. Factors simultaneously influencing palm oil supply include the previous year's palm oil price, the previous year's urea fertilizer price, the previous year's cocoa price, harvested area, and rainfall. The variable with a partially significant influence is the harvested area. If the area of ​​oil palm harvest increases by 1 percent, the supply of oil palm also increases by 0.276 percent per year. The elasticity value of the area of ​​oil palm harvested commodities in the short term is 3.50 and the long term is 4.38 elastic while rainfall has an elasticity value with a value of 0.39 in the short term and 0.49 in the long term on the supply of oil palm commodities in West Sulawesi.